Linking geographic origin and mitogenomes of the ground pangolin in southern Africa - Du Toit, Zelda (University of the Free State, 2021)
The order Pholidota includes the most trafficked mammal species globally. The family Maninae with recognized species are categorized as Endangered and Critically Endangered on the IUCN Red List of Threatened Species. Due to the sharp decline in Asian pangolin numbers, the shift was towards the African pangolin species, to meet the demand in Asia and in Africa. Subsequently, the status of Smutsiinae has been revised by the IUCN and varies between Vulnerable and Endangered. This study contributes to clarify the genetic status of the four African pangolin species using molecular technologies. The first part of the study aimed to assemble mitogenomes of the four African pangolin species using NGS technologies. Whole mitogenomes were assembled and compared with published mitogenomes available in online databases. Mitogenomes were only available for six of the eight pangolin species. Our results showed different genome lengths for the four species: Temminck’s pangolin (16 558 bp), giant pangolin (16 540 bp), white-bellied pangolin (16 565 bp) and black-bellied pangolin (16 649 bp). Three distinctive clusters were observed supporting three genera. The first cluster consisted of the Asian pangolins (Manis), the second cluster was the African tree pangolins (Phataginus) and the third cluster represented the African ground pangolins (Smutsia). There were also two insertions found in the control region of the black-bellied pangolin which could indicate a recent mutation or selection event. The second part of the study focused on the development of species-specific STRs for Temminck’s pangolin and in combination with previous developed mtDNA markers the aim was to assess the population structure across the distribution range in southern Africa. Three mtDNA loci were analysed (Co1, Cytb, control region) with 30 STRs. A total of 62 individuals from six countries were included in the study. The results showed little to no geographical differentiation across the identified sampling locations. This indicates high levels of gene flow between the populations. Three distinctive clusters were observed within the different sampling areas. This could indicate inherited ancestral traits in juveniles with dispersal into new home ranges following a stepping stone model. Temminck’s pangolin has been reported to cover vast distances in search of new home ranges or territories. This study provides the first account of a combination of mtDNA and STR markers to investigate possible geo-referencing of Temminck’s pangolin in southern Africa. It is evident that the mtDNA and STRs markers used in this study, are not robust enough to discriminate between different sampling locations or populations. Further in-depth investigations, including whole genome analysis and SNPs are recommended. A more comprehensive sampling strategy is required to include all areas within the distribution range as well as more individuals for an in-depth genome analyses.
Keywords: Thesis (Ph.D. (Genetics))--University of the Free State, 2021; Mitochondrial genomes; Microsatellites; Geo-referencing; African pangolins